Characteristic diagnosis of supersonic gas jet target for laser wakefield acceleration with high spatial-temporal resolution Nomarski interference system - Liu, Qiushi; Ma, Mingjiang; Zhang, Xiaohua; Lv, Chong; Song, Jianmin; Wang, Zhao; Yang, Guoqing; Yang, Yanlei; Wang, Jiahao; Li, Qinxiang; Zhao, Baozhen (Frontiers in Physics, 2023)
Gas targets hold distinctive significance and advantages in the field of laser-matter interaction.As a major type of gas targets, supersonic gas target is one of the most commonly used targets for laser wakefield acceleration (LWFA). The temporal-spatial resolution study of it could provide valuable data references for the LWFA experiment. In this work, a Nomarski interference system with high spatial-temporal resolution was set up to diagnose the jet process of supersonic gas jet target. The formation process of supersonic gas jet under different jet durations, different injection positions and different gas back pressures was studied. It is beneficial to determine the more optimized time and position of laser injection into target when conducting LWFA experiments.Therefore, the quality of the obtained electron beam and radiation source can be effectively improved.